POSTMODERNO RECIKLIRANJE FANTAZAMA U ROMANU DUBRAVKE UGREŠIĆ BABA JAGA JE SNIJELA JAJE (2008) (Филолошке студије, 2019)
The paper focusses on three fantastic figures of the last book of Croatian author Dubravka Ugrešić Baba Jaga je snijela jaje 2008. (English translation: Baba Yaga Laid An Egg, Edinburgh: Canongate, 2009.), that is, the fantasies of birds, Baba Yaga and the egg. Thus, this work investigates how traditional imaginary figures have been recycled in the postmodern women writing. Interpretation is ran in the perspective of psychoanalytical theory, using single concepts of S. Freud, M. Klein, J. Lacan, J. Kristeva, Sl. Žižek, J. Buthler. Ugrešić’s fantastic images have been also compared with similar fantastic representations in film –. Hitchcock’s Birds, or in painting – F. Kahlo’s self-portrait. Research shows that, in comparison with their folklore archetypes, the recycled literary fantasies of Ugrešić have been basically inverted: they imply subversion and irony that are directed not only against the dominant models of public taste and the forms of contemporary “soft” ideologies but also against the traditional roles of reader, writer, critic and text as places where a narrative happens and a coherent meaning has to be produced.